Characterization and Fine Mapping of qRPR1-3 and qRPR3-1, Two Major QTLs for Rind Penetrometer Resistance in Maize - Hou, Xinwei; Cheng, Senan; Wang, Shukai; Yu, Ting; Wang, Yancui; Xu, Pingping; Xu, Xitong; Zhou, Qi; Hou, Xuetong; Zhang, Guobin; Chen, Cuixia (Frontiers in Plant Science, 2022)
Stalk strength is one of the most important traits in maize, which affects stalk lodging resistance and consequently maize harvestable yield. Rind penetrometer resistance (RPR) as an effective and reliable measurement for evaluating maize stalk strength is positively correlated with stalk lodging resistance. In this study, one F2 and three F2:3 populations derived from the cross of inbred lines 3705I (low RPR line) and LH277 (high RPR line) were constructed for mapping quantitative trait loci (QTL) conferring RPR in maize. 14 RPR QTLs were identified in four environments and explained the phenotypic variation of RPR from 4.14 % to 15.89 %. By using a sequential fine-mapping strategy based on progeny test, two major QTLs qRPR1-3 and qRPR3-1 were narrowed down to 4 Mb and 550 kb genomic interval respectively. Quantitative Real-time PCR (qRT-PCR) assay was adopted to identify 12 candidate genes responsible for QTL qRPR3-1. These findings should facilitate the identification of the polymorphism loci underlying QTL qRPR3-1 and molecular breeding for RPR in maize.